The Development Of An Autonomous Social Science Tradition In Asia: Problems And Prospects. - Alatas, Syed Hussein (Brill Academic Publishers., 2002)
Since my student days at the University of Amsterdam, in the early fifties, I have been intuitively concerned with the need for an autonomous social science tradition in the various regions of the world. During that period, on reading Ibn Khaldun, I was told that art could not develop without artists. By the same token, an autonomous tradition cannot develop without the commitment of an intellectual, creative and independent group striving for that tradition.